Treatment of Atrial Fibrillation in Patients with Co-existing Heart Failure and Reduced Ejection Fraction: Time to Revisit the Management Guidelines? - Baher, Alex (Arrhythm Electrophysiol Rev, 2018)
AF in patients with heart failure and reduced ejection fraction (HFrEF) is common and is associated with an increased risk of stroke, heart failure hospitalisation and all-cause mortality. Rhythm control of AF in this population has been traditionally limited to the use of antiarrhythmic drugs. Clinical trials assessing superiority of pharmacological rhythm control over rate control have been largely disappointing. Catheter ablation has emerged as a viable alternative to pharmacological rhythm control in symptomatic AF and has enjoyed significant technological advancements over the past decade. Recent clinical trials have suggested that catheter ablation is superior to pharmacological interventions in patients with co-existing AF and HFrEF. In this article, we will review the therapeutic options for AF in patients with HFrEF in the context of the latest clinical trials beyond the current established guidelines.